Efektivitas Sosialisasi Lapak Desa terhadap Pemasaran Online (E-Commerce) Berbasis Syariah - Alfina Shafira; Muhammad Iqbal Fasa; Soeharto Soeharto; Rio Kartika Supriyatna; Dedi Junaedi (LPPM Institut Nasional Laa Roiba Bogor, 2021)
Socialization of activities is carried out by visiting the community or business owners directly and providing information related to this village website. Evaluation of activities, visiting the community and digging up information about community knowledge in conducting information and education must be continuously conveyed to the community, and supervision must also be carried out so that the community is educated and has the ability to operate technology. In fact, digital marketing launched by Tiyuh Pulung Kencana has a large commercial impact on business if it is implemented through various targeted assistance and socialization. In addition, essentially in Islam the muamalah system is based on permissibility/permissibility. However, the low willingness and understanding of the SME group in the use of information technology as a means to market their products is one of the obstacles faced when carrying out this socialization.